Design of Server Software of Automatic Recycling and Dispatching System for Portable Gas Detector - FENG Hang; HU Yu (Gong-kuang zidonghua, 2012)
The paper introduced workflow and network model of automatic recycling and dispatching system for portable gas detectors, and described design and implementation of server software of the system. The software uses MySQL database to manage and maintain the data, uses Qt4.7 platform to develop graphical user interface, and achieves effective management of portable gas detector, instrument administrators and users.